2003
DOI: 10.1109/mcg.2003.1185574
|View full text |Cite
|
Sign up to set email alerts
|

Enabling a continuum of virtual environment experiences

Abstract: The virtuality continuum. 2 A 360-degree ARC with capability for 3D sound and haptic devices. 3 Users within the ARC have turned their body toward a real silvered ball painted with optical material and are engaged in an augmented reality experience with a remote user. Projects in VR 4 March/April 2003 4 (a) A user experiencing augmented reality (in the ARC) on a Human Patient Simulator used in training medics on various emergency procedures. (b) A user standing in the ARC studies a floating 3D model of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…There remains the question of managing this augmentation of virtuality i.e. managing traversals or transitions within the virtuality continuum as discussed by Davis et al [6]. Most research has examined mixed reality boundaries [2] where physical boundaries mark crossovers between mixed and virtual reality [8].…”
Section: Blended / Mixed Realitymentioning
confidence: 99%
“…There remains the question of managing this augmentation of virtuality i.e. managing traversals or transitions within the virtuality continuum as discussed by Davis et al [6]. Most research has examined mixed reality boundaries [2] where physical boundaries mark crossovers between mixed and virtual reality [8].…”
Section: Blended / Mixed Realitymentioning
confidence: 99%
“…The HMPD technology has also been explored in multiuser collaborative environments. For instance, Rolland et al 20 and Davis et al 25 have demonstrated a deployable room display environment for medical training. By exploring several unique properties inherent in HMPD technology, Hua et al have developed a multiscale collaborative infrastructure, referred to as SCAPE, to support versatile modes of user interaction and collaborative operation in augmented virtual environments.…”
Section: Related Workmentioning
confidence: 99%
“…The rVA experiments were conducted within an augmented reality visualization center (ARC) shown in Figure 2. The ARC is a prototype multi-modal augmented reality system with 3D visual, 3D audio and haptic capabilities configured as a quasi-circle of 4.57 m (15 ft) diameter (Davis, Rolland, Hamza-Lup, & Ha, 2003;Rolland, Stanney, et al 2004). The display consisted of a curved wall of retroreflective material, and a Linux-based PC.…”
Section: Methodology Application: Projection Hmdmentioning
confidence: 99%